ANALISIS PERAN GURU DALAM PELAKSANAAN PEMBELAJARAN JARAK JAUH DI SEKOLAH DASAR SEKECAMATAN CARINGIN SUKABUMI TAHUN PELAJARAN 2020/2021 - Erni Nurjanah; Dewi Fitriani; Nursani Maesaroh (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study was carried out to determine the procedure followed by teachers in the implementation of distance learning in elementary schools in the year 2020/2021, as well as the role of teachers in the implementation of distance learning in elementary schools in the year 2020/2021. The qualitative descriptive research model is used in this study. The teacher was given a questionnaire to learn about the process of distant learning and interviews to learn about various indications of the role of teachers in this study, which was done in an elementary school in the Caringin sub-district, the role of teachers as educators, the role of teachers as community translators, the role of teachers as learning resources, the role of teachers as educators, the role of teachers as educators, the role of teachers as motivators, the role of teachers as mediators or facilitators, and the role of teachers as evaluators. According to the findings of study conducted during the Covid-19 epidemic, teachers' roles in engaging with students are impacted, but teachers are still capable of performing well in the application of distant learning. The function of the instructor is irreplaceable, and parents serve as mentors. Keywords: Teacher Role, Distance Learning